2014
DOI: 10.1093/mp/ssu006
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Auxin Homeostasis Caused by Mitochondrial FtSH4 Gene-Mediated Peroxidase Accumulation Regulates Arabidopsis Architecture

Abstract: Reactive oxygen species and auxin play important roles in the networks that regulate plant development and morphogenetic changes. However, the molecular mechanisms underlying the interactions between them are poorly understood. This study isolated a mas (More Axillary Shoots) mutant, which was identified as an allele of the mitochondrial AAA-protease AtFtSH4, and characterized the function of the FtSH4 gene in regulating plant development by mediating the peroxidase-dependent interplay between hydrogen peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 70 publications
3
55
0
Order By: Relevance
“…This suppression of auxin signaling by mitochondrial ROS positions mitochondria as an important hub in the cellular signaling cascade that can block auxin signaling and thus, play a central role in determining if cellular resources are used for growth (signaled by auxin) or stress resistance (signaled by ROS). Other studies have shown an interaction between mitochondrial dysfunction and auxin signaling (Tognetti et al, 2010;Zhang et al, 2014). Also, blocking auxin action restores, in part, the induction of AOX1a in a rao1/cdke1 mutant background (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This suppression of auxin signaling by mitochondrial ROS positions mitochondria as an important hub in the cellular signaling cascade that can block auxin signaling and thus, play a central role in determining if cellular resources are used for growth (signaled by auxin) or stress resistance (signaled by ROS). Other studies have shown an interaction between mitochondrial dysfunction and auxin signaling (Tognetti et al, 2010;Zhang et al, 2014). Also, blocking auxin action restores, in part, the induction of AOX1a in a rao1/cdke1 mutant background (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…5), further showing the interaction between mitochondrial and auxin signaling. Although the interaction of mitochondrial retrograde signaling with several other pathways has been documented (Schwarzländer and Finkemeier, 2013), especially with other plant hormones such as ABA, a direct interaction between auxin and mitochondrial ROS signaling is only beginning to emerge (He et al, 2012;Zhang et al, 2014). A recent comprehensive study of plastid retrograde signaling also implicated auxin responses in a core of 30 genes that are responsive in a variety of different chemical treatments and genetic mutants associated with plastid dysfunction (Glaßer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Zhang et al (2014a) confirmed our observations linking the lack of FTSH4 protease, oxidative stress, and alternations in plant development and architecture. These authors also revealed additional nonmitochondrial players such as cytoplasmic peroxidases and auxin homeostasis (Zhang et al, 2014a(Zhang et al, , 2014b. They proposed that FTSH4 mediates the peroxidase-dependent interplay between hydrogen peroxide and auxin homeostasis to regulate plant growth and development.…”
mentioning
confidence: 98%
“…By screening for more axillary shoot mutants, mitochondrial AAA-protease AtFtSH4 was identified. Loss of FtSH4 function resulted in a reduction in protein stability in the mitochondria and increased H 2 O 2 levels , which may be used for peroxidase-mediated oxidation of indole-3-acetic acid and cause excessive axillary branches and a dwarf phenotype (Zhang et al, 2014b). Also overexpression of mitochondrial AtPHB3 or MRR/ROS-signaling target gene UGT74E2 (an auxin glycosyltransferase) results in profuse shoot branching (Van Aken et al, 2007;Tognetti et al, 2010).…”
Section: Mtros and Plant Hormone Signalingmentioning
confidence: 99%